New records of Biemna Gray, 1867 (Biemnidae: Biemnida: Demospongiae) and a replacement name for the species Biemna microstyla Thomas, 1984 - Cavalcanti, Thaynã; Neto, Carlos Santos; Pinheiro, Ulisses (Zootaxa, 2018)
Biemna Gray, 1867 is characterized by stylote or exceptionally oxeote megascleres arranged in a plumoreticulate skeleton, ectosomal skeleton consists of the brushed endings of choanosomal tracts, microscleres are sigmas, microxeas, commata and raphides (Hajdu & Van Soest 2002). Currently, Biemna has 55 valid species (Van Soest et al. 2018). In Brazil, three species are known from northern region (Muricy 2018): Biemna microacanthosigma Mothes, Hajdu, Lerner & Van Soest, 2004, Biemna spinomicroxea Mothes, Campos, Lerner, Carraro & Van Soest, 2005, Biemna trisigmata Mothes & Campos, 2004. In this present study, a new name is proposed for a preoccupied combination, Biemna thomasi nom. nov. The species Biemna caribea Pulitzer-Finali, 1986 is recorded and described for the first time in Brazilian waters. Six specimens of Biemna were studied in Pernambuco and Bahia States. All specimens were preserved in 80% ethanol and deposited on the Porifera Collections at the Universidade Federal de Pernambuco (UFPEPOR).